The Growth and Yield of Upland Rice (Oryza sativa L.) Applied by Rice Husk Zeolite and Potassium Fertilizer - Nelvia Nelvia; Idwar Idwar; Zulfatri Zulfatri; Desra Winri (UNIVERSITY OF LAMPUNG, 2024)
The productivity of upland rice on sub-optimal land such as Ultisol is low. Increasing rice productivity can be attempted, for example, by applying rice husk zeolite and K fertilizer. This research aims to study the interaction of rice husk zeolite with K fertilizer on the growth and yield of upland rice on Ultisol. The research was conducted at the Soil and Greenhouse Laboratory, Faculty of Agriculture, University of Riau, from June to October 2022. The research was conducted experimentally in a factorial with a completely randomized design (CRD). The first factor was rice husk zeolite consisting of 3 levels (0, 200, and 400 kg ha-1), and the second factor was K fertilizer consisting of 3 levels (0, 50, and 100 kg K2O ha-1), each interaction repeated three times. The results showed that the combination value of rice husk zeolite at a dose of 200 kg ha-1 with K fertilizer at a dose of 50 kg K2O ha-1 increased the number of healthy grains per panicle by 21%, the proportion of healthy grain by 14% and the weight of dry milled grain by 32.25% compared to without rice husk zeolite and K fertilizer.